Study and Evaluation of Drainage Water Quality for the Upper Al_Masab Al_A'am Channel (Journal of University of Babylon for Engineering Sciences, 2018)
There is water shortage problem in Euphrates River, with the water quality problem of river water. The important cause behind that need to monitor water quality to verify whether the examined water quality suitable for intended usage or not. The study is conducted Abo-Ghareeb to Al-Masib city for Al_Masab Al_A'am Channel in Iraq to make valid assessment for level of parameters measured and realize their effects on irrigation. The collected samples for different elements were analyzed chemically, which affect water quality for irrigation, These elements are Calcium (Ca+2), Sodium (Na+), Magnesium (Mg+2), Chloride (Cl), Potassium (K+), Bicarbonate (HCO3-), Nitrate (NO3-), Sulfate (SO4-2), Phosphate(PO43), Carbonate (CO3-2), Electrical Conductivity (EC), Total Dissolved Solids (TDS) and pH-values (PH). Sodium Adsorption Ratio (SAR), Sodium Content (Na %) and Residual Sodium Carbonate (RCS) have been also calculated. The Irrigation Water Quality Index (IWQI) will be examined and  upgraded  (integrated  with  GIS) In  order  assess  the  drainage  water quality for irrigation purposes with a high accuracy, to make classification for drainage water. For this purpose, twelve samples of drainage water were taken from different four location of the study area. The results analysis of (IWQI) maps confirms that: 61% of drainage water in study area falls within "Low restriction" and 36% of study area has water with (Moderate restriction), While 3% of drainage water in study area classified as (Sever  restriction). So, the drainage water should use with soil having high permeability with some constraints imposed on types of plant for specified tolerance of salts.